Inflammatory markers in Eisenmenger syndrome and their association with clinical outcomes. A cross-sectional comparative study. (1st November 2021) - Gonzaga, Laion R.A.; Gomes, Walter J.; Rocco, Isadora S.; Matos-Garcia, Bruna C.; Bublitz, Caroline; Viceconte, Marcela; Tatani, Solange B.; Santos, Vinicius B.; Silva, Célia M.C.; Tulloh, Robert; Arena, Ross; Guizilini, Solange
Abstract: Background: Inflammation may be an important factor contributing to the progression of Eisenmenger syndrome (ES). The purpose of the current study was to: characterize the inflammatory profile in ES patients and compare measures to reference values for congenital heart disease and pulmonary arterial hypertension (CHD-PAH); and investigate whether inflammatory markers are associated with other clinical markers in ES. Methods: Twenty-seven ES patients were prospectively selected and screened for systemic inflammatory markers, including interleukin (IL)-1β, tumor necrosis factor-alpha (TNF-α) and IL-10. Clinical data and echocardiographic parameters were obtained, with concomitant analysis of ventricular function. Functional capacity was assessed using the 6-min walk test (6MWT). Renal function and blood homeostasis were evaluated by the level of blood urea nitrogen (BUN), creatinine, and plasma electrolytes. Results: Patients with ES expressed higher IL-10, IL-1β and TNF-α compared to reference values of patients with CHD-PAH. IL-10 was negatively associated with BUN (r = −0.39, p = 0.07), creatinine (r = −0.35, p = 0.002), sodium (r = −0.45, p = 0.03), and potassium (r = −0.68, p = 0.003). IL-10 was positively associated with bicarbonate (r = 0.45, p = 0.02) and trended toward a positive association with right ventricular fractional area change (RVFAC ) (r = 0.35, p = 0.059). IL-1β was negatively associated with potassium (r = −0.5, p = 0.01). TNF-α demonstrated positive association with creatinine (r = 0.4, p = 0.006), BUN (r = 0.63, p = 0.003), sodium (r = 0.44, p = 0.04), potassium (r = 0.41, p = 0.04), and was negatively associated with RVFAC (r = −0.38, p = 0.03) and 6MWT distance (r = −0.54, p = 0.004). Conclusion: ES patients exhibit a more severe inflammatory profile compared to reference values for CHD-PAH. Furthermore, inflammatory markers are related to renal dysfunction, right ventricular impairment and poorer functional capacity. Highlights: ES is the most severe manifestation of elevated pulmonary resistance. ES expressed an exacerbated inflammatory profile compared to congenital heart disease. Inflammatory status is related to the right heart, renal, and exercise performance in ES.